1997
DOI: 10.1159/000213864
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Presentation of Peptic Ulcer in the Elderly

Abstract: The aim of this study was to determine the age-related characteristics of peptic-ulcer patients. A total of 125 consecutive patients (63 men and 62 women) with peptic ulcer were studied prospectively. The ulcers were diagnosed at endoscopy. The mean age of patients was 62 years (57 years in men and 68 in women). Patients were asked about their use of nonsteroidal anti-inflammatory drugs (NSAIDs). The main symptom, the duration of symptoms, the ulcer location and size, and the presence of Helicobacter pylori (H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
14
0
1

Year Published

1998
1998
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(19 citation statements)
references
References 14 publications
4
14
0
1
Order By: Relevance
“…Our results show that elderly patients with HP infection had, as expected, a higher prevalence of peptic ulcer disease and higher titres of IgG anti-HP antibodies. These findings were in agreement with recent studies demonstrating that, in elderly subjects, HP infection is associated with clinically important gastroduodenal pathologies [24,25]. HP eradication reduces both short-and long-term symptomatology, gastritis activity and ulcer recurrences [26,27].…”
Section: Discussionsupporting
confidence: 93%
“…Our results show that elderly patients with HP infection had, as expected, a higher prevalence of peptic ulcer disease and higher titres of IgG anti-HP antibodies. These findings were in agreement with recent studies demonstrating that, in elderly subjects, HP infection is associated with clinically important gastroduodenal pathologies [24,25]. HP eradication reduces both short-and long-term symptomatology, gastritis activity and ulcer recurrences [26,27].…”
Section: Discussionsupporting
confidence: 93%
“…Histopathologic and epidemiologic studies showed that gastric cancer may be associated with hyperproliferation of gastric cells (Kemppainen et al, 1997;Persing and Prendergast, 1999) and this hypothesis was proven in studies on Helicobacter pylori infection (Correa, 1997;Guarner et al, 1993;Lynch and Axon, 1995;Moss, 1999). Increased proliferation of gastric cells by Helicobacter pylori was inhibited by supplementation of antioxidants and NF-B inhibitors (Bukin et al, 1993;Sharma et al, 1995).…”
Section: Discussionmentioning
confidence: 94%
“…That is, the prevalence of H. pylori-negative peptic ulcers in the USA and Australia is relatively high, at 27-43%, and relatively low in Europe and Japan, at 2.7-8.0% [31][32][33][34][35][36]. This could be explained from the fact that the infection rate of H. pylori fell more rapidly in the USA and Australia.…”
Section: Discussionmentioning
confidence: 99%